Predictability and Patentable Processes: The Federal Circuit’s In re Bilski Decision and Its Effect on the Incentive to Invent - Schuster, William Michael (Science and Technology Law Review, 2009)
Throughout the past two centuries, the U.S. patent system has defined the scope of (potentially) patentable processes by proscribing patents on fundamental principles (including abstract ideas, laws of nature, and natural phenomena). Unfortunately, such a description of patentable subject matter led to ambiguity and unpredictability in the application of the patent laws. In 2008, the Federal Circuit addressed this uncertainty by promulgating a new standard to describe the ambit of patentable processes: a process may constitute patentable subject matter if (1) it utilizes a particular machine or apparatus, or (2) it transforms an object into a different state or thing. This Article describes how the Federal Circuit’s new standard furthers the underlying policy goal of all patent laws: the incentivization of innovation. Specifically, this paper argues that this new rule presents a simple and easy to apply standard that will increase the predictability of the patent laws. In the presence of such predictability, prospective inventors and investors are more likely to engage in research and development, thus leading to increased inventive activity.